Faktor-Faktor yang Mempengaruhi Perilaku Penerapan Protokol Kesehatan Covid-19 pada Warga RT.005 RW.003 Jatisari, Bekasi - Josua Geloni; Elwindra Elwindra (STIKes Persada Husada Indonesia, 2022)
The world is shocked by the emergence of a new type of virus, known as the coronavirus. Coronaviruses (CoV) are part of a family of viruses that cause illness ranging from the flu to more severe illnesses such as Middle East Respiratory Syndrome (MERS-CoV) and Severe Acute Respiratory Syndrome (SARS-CoV). It is known that preventive efforts are the best for citizens to avoid exposure to the Covid-19 virus, by implementing health protocols and implementing PHBS (Clean and Healthy Living Behavior). This study aims to determine the factors that influence the behavior of implementing the Covid-19 health protocol in residents of RT 005 RW. 003 Jatisari Bekasi. This research is a quantitative research with analytical method using cross sectional approach. The population in this study were the heads of families in RT. 005 RW. 003 Jatisari Bekasi totaling 203 heads of families. The number of samples calculated by the Slovin formula was taken as many as 75 families, data collection by accidental sampling. Data analysis used in this research is univariate and bivariate analysis using Chi Square. The results showed that there was a significant relationship between knowledge and behavior with P-Value 0.011 (>0.05), attitude and behavior with P-Value 0.044 (>0.05) and personal health protocol facilities with behavior with P-Value 0.23 (>0.05). In conclusion, residents of RT. 005 RW. 003 Jatisari Bekasi who have good knowledge, attitudes, and health protocol facilities tend to behave better in implementing the Covid-19 health protocol. It is recommended for residents to always be active in implementing clean and healthy living behaviors and following the health protocol system, and continue to seek information about the Covid-19 virus pandemic through trusted information sources.